The link between exposure to violence and psychological distress among middle-aged Muslims in Israel: the role of gender - Iktilat, Khalil; Isacson, Michal; Tzemah-Shahar, Roy; Agmon, Maayan (Frontiers in Public Health, 2024)
Introduction To date, it is still unclear if exposure to violence affects psychological distress in middle-aged adults and if the effects are gender specific. This age group is of special interest as it is at the onset of the aging process and is often overlooked or understudied in scholarly research. Specifically, targeted research on middle-aged Muslims living in Israel, a unique population exposed to increasing violence, is lacking. Methods We examined the relationship between exposure to violence and psychological distress in a cohort of 363 middle-aged adults (223 women) from three Muslim villages in northern Israel, collecting data on violence exposure (Screen for Adolescent Violence Exposure (SAVE) questionnaire), psychological distress (Kessler 6 Psychological Distress questionnaire), and other demographic characteristics including education level and socioeconomic status. We used this data to answer two questions: (1) is exposure to violence a predictor of psychological distress in middle-aged Muslims, and (2) does the relationship between exposure and distress differ between men and women? Results We revealed a positive link between exposure to violence and psychological distress (β = 0.145, p = 0.017) when controlling for gender, age, education level, and socioeconomic level. Discussion Despite previous evidence of gender-based differences in this interplay in younger cohorts, we did not find a significant interaction between gender and the violence exposure-psychological distress interplay. Our findings are some of the first to focus on middle-aged individuals and show that both men and women exhibit connections between exposure to violence and psychological distress when considering covariates. This research provides insights that can be used when planning community-wide interventions and treatment schemes to support healthy aging.